Advances in Integrated and Sustainable Supply Chain Planning: Concepts, Methods, Tools and Solution Approaches toward a Platform for Industrial Practice - Laínez-Aguirre, José Miguel (Springer, 2015)
Decision making at the enterprise level often encompass not only production operations and product R&D, but other strategic functions such as financial planning and marketing. With the aim of maximizing growth and a firm’s value, companies often focus on co-ordinating these functional components as well as traditional hierarchical decision levels. Understanding this interplay can enhance enterprise capabilities of adaptation and response to uncertainties arising from internal processes as well as the external environment.